Magnetic Resonance and Its Applications - Chizhik, Vladimir I.; Chernyshev, Yuri S.; Donets, Alexey V.; Frolov, Vyacheslav V.; Komolkin, Andrei V.; Shelyapina, Marina G. (Springer International Publishing : Imprint: Springer, 2014)
The book is devoted to the description of the fundamentals of various radiospectroscopic methods in the area of magnetic resonance and their use for the investigation of molecular structure and dynamics and for some technical applications. This book covers two domains: radiospectroscopy and quantum radioelectronics. Radiospectroscopy comprises nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR), nuclear quadrupolar resonance (NQR), and some other phenomena. The radiospectroscopic methods are widely used for obtaining the information on internal (micro and macro) structure of objects investigated. There are no direct analogues of magnetic relaxation processes among the physical phenomena that define spectra in infrared, visible and higher frequency spectroscopy. Relaxation parameters are directly related to molecular mobility and thus represent an unique source of information on velocity and types of thermal motion. One of the most spectacular developments is the concept of double (multi) resonances (NMR-ESR, NMR-NQR, NMR-NMR and so on).             Quantum radioelectronics, which was developed on the basis of radiospectroscopic methods, deals with processes in quantum amplifiers, generators and magnetometers. These devices possess record-breaking characteristics: quantum generators demonstrate the highest frequency stability; quantum amplifiers possess the lowest level of set noise; quantum magnetometers are very fruitful tool for measuring weak magnetic fields (such as the Earth field).             The introductory chapter provides the necessary underpinning knowledge for newcomers to the methods. The exposition of theoretical materials goes from initial to final formulas through detailed intermediate expressions.